An Efficient Protocol for the Synthesis of Novel 1, 2, 3‐Triazole Substituted 4H‐Chromene Derivatives. (17th April 2014) - Sambasiva Rao, P.; Malla Reddy, G.; Kurumurthy, C.; Veeraswamy, B.; Santhosh Kumar, G.; Shanthan Rao, P.; Narsaiah, B.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>